2017
DOI: 10.1038/cddis.2017.483
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of RIP3 by the transcription factor Sp1 and the epigenetic regulator UHRF1 modulates cancer cell necroptosis

Abstract: Receptor-interacting kinase-3 (RIP3) is a key regulator of necroptosis. It has been shown that the expression of RIP3 is silenced in most cancer cells and tissues due to genomic methylation. However, the regulatory mechanisms controlling RIP3 expression in cancer cells have not been fully elucidated. Here, we report that Sp1, a well-characterized zinc-finger transcription factor, directly regulates RIP3 expression in cancer cells. Knockdown of endogenous Sp1 significantly decreases the transcription of Rip3, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 40 publications
1
52
0
1
Order By: Relevance
“…In that study, the cancer cell lines that showed lack of RIP3 expression were found to be resistant to the combination of TNFα, Z-VAD-FMK and the SMAC mimetic SM-164. Similarly, in another study where 8 colon cancer cell lines were tested for sensitivity to a TNFα, SMAC mimetic and Z-VAD-FMK combination, only those that were devoid of RIP3 at the mRNA and protein levels failed to undergo necroptosis (50). Consistent with these results, our data suggest that RIP3 loss can be an underlying mechanism by which HNSCCs become resistant to necroptotic death stimulated with Birinapant and Z-VAD-FMK (Fig 4A-G).…”
Section: While Previous Reports Have Demonstrated That Smac Mimetics supporting
confidence: 87%
“…In that study, the cancer cell lines that showed lack of RIP3 expression were found to be resistant to the combination of TNFα, Z-VAD-FMK and the SMAC mimetic SM-164. Similarly, in another study where 8 colon cancer cell lines were tested for sensitivity to a TNFα, SMAC mimetic and Z-VAD-FMK combination, only those that were devoid of RIP3 at the mRNA and protein levels failed to undergo necroptosis (50). Consistent with these results, our data suggest that RIP3 loss can be an underlying mechanism by which HNSCCs become resistant to necroptotic death stimulated with Birinapant and Z-VAD-FMK (Fig 4A-G).…”
Section: While Previous Reports Have Demonstrated That Smac Mimetics supporting
confidence: 87%
“…Next, the intestinal epithelial cell line HCT116, which lacks RIPK3 expression , was used to clarify the role of RIPK3 in the increased LC3 puncta observed following TNF‐α plus Z‐VAD treatment. To confirm RIPK3 dependency of this phenomenon, Myc‐RIPK3 was introduced into HCT116 cells and the LC3 puncta in Myc‐expressing cells were analyzed (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, tumors continue to grow and increase in numbers. Ectopic RIPK3 expression in a lung cancer cell line induced cell death to reduce tumor growth in a xenograft model (41). In contrast, RIPK3 deletion in breast and colon cancer cell lines reduced tumor growth in xenograft models (30).…”
Section: Discussionmentioning
confidence: 99%